HUBUNGAN INDEKS MASA TUBUH (IMT) TERHADAP KADAR HEMOGLOBIN PADA PASIEN TUBERKULOSIS PARU DI RUMAH SAKIT UMUM SULTAN SULAIMAN KABUPATEN SERDANG BEDAGAI - Sahara, Eriani; Sartini, Sartini; Nugrahalia, Meida (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2015)
Tuberculosis (TB) is a respiratory disease that received special attention in the community. According to WHO more than 2 million people, one third of the total population in the world is infected by tuberculosis. Tuberculosis patients with malnutrition status have lower haemoglobin levels compared to patients with good nutritional status. The purpose of this reseach is to determine the relationship of body mass index (BMI) to the haemoglobin of patients pulmonary tuberculosis at the General Hospital Sultan Sulaiman Serdang Bedagai. This study was conducted descriptive of examination BMI and levels of haemoglobin in patients with pulmonary tuberculosis at the General Hospital Sultan Sulaiman Serdang Bedagai North Sumatra Province is to create the relationship between baseline BMI and BMI end after the OAT, as well as haemoglobin beginning and haemoglobin end after the OAT. The results showed that there was a weak correlation between baseline BMI of the initial haemoglobin levels with a value of r = 0.20. While the relationship between BMI end of the final haemoglobin levels after administration of OAT for 2 months there was a strong relationship r = 0.83.